The Endophytic Root Microbiome Is Different in Healthy and Ralstonia solanacearum-Infected Plants and Is Regulated by a Consortium Containing Beneficial Endophytic Bacteria - Yiting Li; Gaofu Qi; Ziqiong Xie; Baolong Li; Rui Wang; Jun Tan; Heli Shi; Bikun Xiang; Xiuyun Zhao (Microbiology Spectrum, 2023)
ABSTRACT Plant bacterial wilt disease caused by Ralstonia solanacearum leads to huge economic losses worldwide. Endophytes play vital roles in promoting plant growth and health. It is hypothesized that the endophytic root microbiome and network structure are different in healthy and diseased plants. Here, the endophytic root microbiomes and network structures of healthy and diseased tobacco plants were investigated. Composition and network structures of endophytic root microbiomes were distinct between healthy and diseased plants. Healthy plants were enriched with more beneficial bacteria and bacteria with antagonistic activity against R. solanacearum. R. solanacearum was most abundant in diseased plants. Microbial networks in diseased plants had fewer modules and edges, lower connectivity, and fewer keystone microorganisms than those in healthy plants. Almost half of the nodes were unique in the two networks. Ralstonia was identified as a key microorganism of the diseased-plant network. In healthy plants, abundant bacteria and biomarkers (Pseudomonas and Streptomyces) and keystone microorganisms (Bacillus, Lysobacter, and Paenibacillus) were plant-beneficial bacteria and showed antibacterial and plant growth-promoting activities. The endophytic strain Bacillus velezensis E9 produced bacillaene to inhibit R. solanacearum. Consortia containing keystone microorganisms and beneficial endophytic bacteria significantly regulated the endophytic microbiome and attenuated bacterial wilt by inducing systemic resistance and producing antibiotic. Overall, the endophytic root microbiome and network structure in diseased plants were different from those in healthy plants. The endophytic root microbiome of diseased plants had low abundances of beneficial bacteria and an unstable network and lacked beneficial keystone microorganisms, which favored infection. Synthetic microbial consortia were effective measures for preventing R. solanacearum infection. IMPORTANCE Bacterial wilt disease causes heavy yield losses in many crops. Endophytic microbiomes play important roles in control of plant diseases. However, the role of the endophytic root microbiome in controlling bacterial wilt disease is poorly understood. Here, differences in endophytic root microbiomes and network structures between healthy and diseased tobacco plants are reported. A synthetic microbial consortium containing beneficial endophytic bacteria was used to regulate the endophytic microbiome and attenuate bacterial wilt disease. The results could be generally used to guide control of bacterial wilt disease.